2007
DOI: 10.1088/0963-0252/16/3/020
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of O-atom kinetics in O2, CO2, H2O and O2/HMDSO low pressure radiofrequency pulsed plasmas by time-resolved optical emission spectroscopy

Abstract: In the present paper, O-atom kinetics is investigated in low pressure (around 0.7 Pa) O 2 /hexamethyldisiloxane pulsed plasmas by time-resolved optical emission spectroscopy. In order to distinguish direct O-atom excitation by electron impact from dissociative excitation of O 2 , CO, CO 2 and H 2 O molecules formed in O 2 /HMDSO plasmas, measurements were first carried out in pure O 2 , CO 2 and H 2 O plasmas. From these measurements it was concluded that direct O-atom excitation by electron impact was the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…Although the dissociative excitation of ground state O 2 likely makes a minor contribution to InormalO*/IAnormalr* measured in the pure O 2 plasma, this pathway can be ignored in the CO 2 and H 2 O plasma systems. Bousquet et al investigated the atomic oxygen excitation kinetics in O 2 , CO 2 , and H 2 O plasmas. They found that production of O* via dissociative excitation of O 2 , CO 2 , CO, H 2 O, or OH in CO 2 and H 2 O plasma systems was negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Although the dissociative excitation of ground state O 2 likely makes a minor contribution to InormalO*/IAnormalr* measured in the pure O 2 plasma, this pathway can be ignored in the CO 2 and H 2 O plasma systems. Bousquet et al investigated the atomic oxygen excitation kinetics in O 2 , CO 2 , and H 2 O plasmas. They found that production of O* via dissociative excitation of O 2 , CO 2 , CO, H 2 O, or OH in CO 2 and H 2 O plasma systems was negligible.…”
Section: Discussionmentioning
confidence: 99%
“…This is preferable to using the O atom density since in this case the effect of gas temperature variations on the total gas density, N, are eliminated. The [O]/N variations were followed by time-resolved actinometry, using Ar (added as 5% of the gas flow) as the actinometer gas [1,3,4,6,[9][10][11]13,[35][36][37][38][39][40][41][42]. The effect of this small addition of Ar on the EEDF and other discharge parameters is negligible, since the EEDF is largely determined by electron collisions with the majority gas, O 2 [43].…”
Section: Measurement Of the O Atom Density Loss Frequency And Surfacmentioning
confidence: 99%
“…Oxygen gas is widely used in many plasma processing applications, and oxygen atoms are one of the key reactive species present in them, leading to recurrent interest in O atom kinetics over a range of different discharge conditions. In low-pressure pure oxygen plasmas these atoms are principally created by electron impact dissociation of O 2 , and predominantly lost by surface recombination; therefore these two processes define the atom density in the plasma volume [1][2][3][4][5][6][7][8][9][10][11][12]. The surface recombination of O atoms has been previously studied on a range of different materials, including dielectrics, semiconductors and metals [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Work done by previous authors has shown that application of the actinometry method does not always yield results that reflect the true atomic oxygen number density in the plasma. The validity of actinometry for atomic oxygen has been investigated for various plasma sources: RF capacitive plasma [14,15,16], ECR source [17], DC glow discharge [18], microwave source [19,20], helicon source [21], inductive source [22], and micro-scale atmospheric pressure jet source [23]. Walkrup et al [14] investigated the validity of actinometry for atomic oxygen in RF capacitive plasmas containing both pure O 2 and O 2 /CF 2 mixtures by examining line emission intensity ratios.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that actinometry using the O * (844)/Ar * (750) emission ratio was valid for modest Ar/O 2 flow ratios (smaller than 2) when the total pressure in their system exceeded 1 Torr while the O * (777)/Ar * (750) ratio gave misleading results. Bousquet et al [21] used actinometry in a low pressure (5 mTorr) pulsed O 2 /Hexamethyldisiloxane helicon source to monitor atomic oxygen density. They determined that direct excitation of atomic oxygen was the main source of emission at 844 nm with only a small contribution due to dissociative excitation of O 2 and that the actinometry technique using the O * (844)/Ar * (750) emission ratio was valid under these experimental conditions provided dissociative excitation of O 2 was also taken into account.…”
Section: Introductionmentioning
confidence: 99%